Analisis Kedudukan Anak Adopsi oleh Orang Tua dari Perkawinan Campuran di Indonesia - Handayani, Imelda Fertikel Putri; Feriska, Mifta Nur; Nugroho, Lucky Dafira (Lembaga Yasin AlSys, 2025)
This study is motivated by the complex legal regulations surrounding child adoption in the context of mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA), particularly when such marriages end in divorce. The primary focus of this research is to analyze the legal status of adopted children in these situations, encompassing issues of citizenship, inheritance rights, and the position of wali nikah (marriage guardian). The objective is to examine the legal standing of adopted children in mixed marriages and the normative implications of disharmony between national and international legal systems on child protection. This study employs a normative legal research method with a descriptive-analytical approach, analyzing relevant regulations, court decisions, and legal literature. The findings reveal that the legal consequences of adoption vary depending on the court that authorizes it: civil court adoptions (adoptio plena) confer legal status and rights equivalent to biological children, while religious court adoptions (adoptio minus plena) provide only limited legal recognition. Moreover, the lack of alignment with the principle of the best interest of the child in the national legal framework results in insufficient legal protection for adopted children. The study concludes that reformulating national adoption laws and harmonizing them with international legal instruments is essential to ensure comprehensive legal protection for adopted children in mixed marriage contexts. Practical implications include policy recommendations for unifying inheritance law systems, strengthening post-adoption monitoring mechanisms, and advocating for child protection in cross-jurisdictional settings. The study also opens avenues for further interdisciplinary research exploring the social and psychological impacts on adopted children in transnational adoption cases.